2015
DOI: 10.5688/ajpe797107
|View full text |Cite
|
Sign up to set email alerts
|

Note-taking and Handouts in The Digital Age

Abstract: Most educators consider note-taking a critical component of formal classroom learning. Advancements in technology such as tablet computers, mobile applications, and recorded lectures are altering classroom dynamics and affecting the way students compose and review class notes. These tools may improve a student's ability to take notes, but they also may hinder learning. In an era of dynamic technology developments, it is important for educators to routinely examine and evaluate influences on formal and informal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
52
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(55 citation statements)
references
References 28 publications
0
52
0
3
Order By: Relevance
“…Teachers need to prepare multiple simultaneous learning tasks for students (Boyle, Rosen, & Forchelli, 2016). Also, they need to guide learner toward managing their own current and future needs (Stacy & Cain, 2015). Findings based on figure 5 indicated an improvement in taking notes as well as support permanent learning when interactive learning environment used in instruction.…”
mentioning
confidence: 99%
“…Teachers need to prepare multiple simultaneous learning tasks for students (Boyle, Rosen, & Forchelli, 2016). Also, they need to guide learner toward managing their own current and future needs (Stacy & Cain, 2015). Findings based on figure 5 indicated an improvement in taking notes as well as support permanent learning when interactive learning environment used in instruction.…”
mentioning
confidence: 99%
“…Some studies support the notion that providing information digitally is compatible with the current student digital expertise and learning comfort level (e.g., Kozma, 1994;Schmid, et al, 2014;Abowd, et al, 1997;Hiltz & Turoff, 2005). Conversely, other theory and literature contends that hardcopy material requires students to actively engage, and thus increases retention (e.g., Stacy & Cain, 2015;Lam, Lam, Lam, & McNaught, 2009). Therefore, due to contradictory theory and literature, regarding the optimal method for student learning, it is important to examine this topic in order to assist faculty when designing their course.…”
Section: Background and Research Question Developmentmentioning
confidence: 89%
“…Moreover, research provides mixed results regarding the optimal delivery method. Although digital information is cost effective, provides easy access, and allows students to review specific material (Wilson, 2003), the hard copy material is found to help students with note-taking (Stacy & Cain, 2015), which in turn increases conceptual understanding (Mueller & Oppenheimer, 2014). With these findings, coupled with the requirement of meeting the demands of the accounting profession, it is important to investigate the effects of digital and hard copy delivery in the accounting classroom.…”
Section: Introductionmentioning
confidence: 99%
“…Considering the hitherto inconsistent findings (e.g. Stacy & Cain, 2015), whether and to what extent this goal has been achieved is yet to be fully determined. Mueller and Oppenheimer (2016) conducted an interesting review of the role of technology in notetaking in four different contexts: classroom, boardroom, hospital room, and courtroom.…”
Section: Related Workmentioning
confidence: 99%